2018
DOI: 10.1160/th17-05-0348
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Elastase-Derived Fibrin Degradation Products Indicate Presence of Abdominal Aortic Aneurysms and Correlate with Intraluminal Thrombus Volume

Abstract: E-XDP is a marker of the presence of AAA and coexisting aneurysms as well as the volume and mechanical stress of the ILT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 352 publications
(589 reference statements)
1
7
0
Order By: Relevance
“…Because leucocyte activation with consequent release of elastin has been shown to participate in the pathophysiology of CVD, it would be reasonable to assume that E-XDP determination would be more specific for CVD than D-dimer. Of note, the assay used in the present study was proven specific for measuring levels of E-XDP generated from fibrin by the proteolytic action of LE (and not plasmin) by Kohno et al and in a study done by our group [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Because leucocyte activation with consequent release of elastin has been shown to participate in the pathophysiology of CVD, it would be reasonable to assume that E-XDP determination would be more specific for CVD than D-dimer. Of note, the assay used in the present study was proven specific for measuring levels of E-XDP generated from fibrin by the proteolytic action of LE (and not plasmin) by Kohno et al and in a study done by our group [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 92%
“…Besides activation of leukocytes, it is possible that the patients have thrombi in other parts of the body or micro thrombi in the vein wall that are also degraded by LE, but other unknown sources of thrombi can not be excluded [ 14 , 23 ]. For example, in a previous study by our group, we observed an association between E-XDP and presence of intraluminal thrombi in patients with abdominal aortic aneurysms [ 18 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…showed that E-XDP, neutrophil elastase had higher concentrations in patients with the presents of AAA and other coexisting aneurysms but popliteal artery aneurysms weren´t specifically studied. 41 The presence of AAAs associated with growth rate could be a surrogate marker for the presence of a more generalized aneurysmal disease and has not been shown by others.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 95%
“…Besides, there is a direct correlation between elastase activity and nicotine concentration [ 114 ]. Recently, studies showed that circulating NE-derived fibrin degradation products are elevated in patients with AAA and correlate with AAA and ILT volume as well as with the mechanical stress of the ILT [ 115 , 116 ]. The role of NE as a postoperative biomarker is controversial.…”
Section: Abdominal Aortic Aneurysms and Neutrophilsmentioning
confidence: 99%